Hayek Vs. Marx: An Extemporaneous Comparison - Feijó, Ricardo Luis Chaves (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2017)
The essay begins by examining the basis of the thoughts of Karl Marx and Friedrich Hayek in that order. In the first case, reference is made to the philosophical debate in Prussia at the turn of the eighteenth and nineteenth centuries, in particular a synthesis of the philosopher Hegel’s reflection. There follows the synthetic exposition of Marx's system. In Hayek, it examines the influences exerted on him by Austrian authors such as Ludwig von Mises and Carl Menger, and then it starts the detailing of the theory of spontaneous order and the connectionist theory of mind. After studying the foundations of the legacy of Marx and Hayek it follows the strategy of confronting the two systems of thought. For this, a systematic comparison between them is offered. In the concluding section, the same contrast of ideas is treated by means of a synoptic table.